Exploring EFL Students’ Lived Experiences Working in Single-Gender and Mixed-Gender Groups: A Phenomenological Study - Mulfina, Emelya Putri; Karmina, Sari; El Khoiri, Niamika (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
Group work (GW) is one of the strategies teachers employ to organize students and let them participate in collaborative tasks to achieve their learning-centered goals. The formation of single-gender (SG) and mixed-gender (MG) groups cannot be avoided in GW.  Thus, this research aimed to explore EFL (English Foreign Language) students’ lived experiences working in SG and MG groups. A qualitative study using a phenomenological approach was conducted. The data were collected from three rounds of semi-structured interviews with eight participants. They were selected through three steps of online screening with some criteria. The research was conducted at one of the state universities in East Java, Indonesia. Van Kaam’s method, modified by Moustakas (1994), was used to analyze the data. This research revealed two main results: positive and negative experiences reported by students in both the SG and MG groups. In the SG group, the themes include effective communication, postponed GW tasks, and a better environment. In contrast, in the MG group, the themes encompass ineffective communication, solid members, and ineffective time management. In short, two positive and one negative theme are mentioned in SG groups, while one positive and two negative themes emerge in MG groups. As a result, the core aspects revealed include communication, individual contributions and responsibility, and productivity and efficiency while working in groups. This present research adds more comprehensive theories of GW related to students' gender and helps students and teachers be more aware of GW related to gender aspects.